Storm of dogs - Hunter, Erin (Harper, an imprint of HarperCollinsPublishers, 2015)
"Lucky and the dogs of the Wild Pack must fight tooth and claw to survive the storm of dogs--the terrifying battle that has been haunting Lucky's dreams"--
750
750L
Keywords: Dogs -- Fiction; Wild dogs -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Dogs -- Juvenile fiction; Wild dogs -- Juvenile fiction; Survival -- Juvenile fiction; Action and adventure fiction; Fantasy fiction